Assessing Vehicular Emission Reduction Potential for Home-based Work-trips for Kathmandu Valley, Nepal - Bajracharya, Ashim Ratna; Shrestha, Sudha (Journal of Engineering Technology and Planning, 2024)
Kathmandu valley is known to be the prime center economic activities and employment opportunities and it has become a major concern to manage work trips to cut down emissions from the urban transport sector. This paper analyses home-based work trips and estimates total emission, resulting from it. The trip data was collected through a household survey, conducted in different parts of the study area, using stratified random sampling, to study how people travel from their homes to work places. The total annual greenhouse gas (GHG) is estimated to be around 186000 ton from work-related trips. The excessive use of private vehicles, which accounts for more than 60% of total trips, significantly contributes to these emissions. Furthermore, the study disaggregates the study area into two parts. The first part, is the area inside ring road, that covers the central part of the valley and second part includes the settlements on the outskirts, outside ring road. The estimates reveal that trips originating from outside the ring road emit GHGs nearly three times more than those within the ring road, primarily due to increased travel distance for peripheral settlements. Consequently, the paper explores possible methods to minimize GHG emissions from work trips, including conventional approaches and the emerging trend of working from home, along with the associated challenges.